Infrared Photodetectors Based on Low-Dimensional Materials - Guo, Nan (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This book is focused on the study of physical mechanisms and device design for achieving high-performance infrared photodetection based on low-dimensional materials. Through theory analysis, material characterization and photo-electric measurements, it provides solutions to the trade-off problems which are commonly encountered in traditional infrared photodetectors and presents novel methods to improve the responsivity, detectivity and response speed. Researchers and scientists in the field of opto-electronic device can benefit from the book.